DETERMINAN PERILAKU KEWARGANEGARAAN ORGANISASIONAL (OCB) PETUGAS DI RUMAH SAKIT - Yohana E Wonga; Nang Among Budiadi; Sugiyarmasto .; Ariefah Yulandari (Fakultas Ekonomi - Universitas Setia Budi, 2020)
This study was aimed to examine the effect of job satisfaction and organizational commitment to OCB, the effect of job satisfaction on organizational commitment, the effect of organizational justice to job satisfaction and organizational commitment, the influence of superordinate support to job satisfaction and organizational commitment. Sample was determided by using probability cluster sampling method and random sampling.The sample were staffs of Psychiatric Hospital and PKU Muhammadiyah Hospital in Surakarta. Data collection using questionnaires was distributed directly as many as 200 questionnaires. Data analysis was conducted by using SEM. The results showed that job satisfaction had a positive effect on OCB, organizational commitment had no effect on OCB. Job satisfaction had no effect on organization commitment. The value of organizational justice to job satisfaction shows significant effect, but not on organizational commitment. Superordinate support had no effect on job satisfaction and organizational commitment.